The Effect of Animated Videos on Flood Disaster Mitigation Knowledge in Children Aged 5-6 Years - Siti Ainun Nasution; Puji Yanti Fauziah (Proceedings of the 1st International Conference on Social Science (ICSS), 2024)
This study aims to: (1) examine the effect of animated videos on flood disaster mitigation knowledge in children aged 5-6 years; (2) compare the effectiveness of animated videos versus conventional learning methods in enhancing flood disaster mitigation knowledge and personal safety among this age group. This quasi-experimental study employed a non-equivalent control group design with a sample of 21 children from PKK 94 Kindergarten and 18 children from Adi Siswa Kindergarten in Bantul Regency. Data were collected through observation and documentation and analyzed using Paired Sample t-test and Independent Sample t-test at a 0.05 significance level. The results indicate that (1) there is a significant improvement in flood disaster mitigation knowledge following the use of animated videos, as evidenced by a Paired Sample t-Test (p = 0.001); and (2) animated videos were more effective than conventional methods, as indicated by the Independent Sample t-Test (p = 0.001). These findings suggest that animated videos are a beneficial tool for teaching flood disaster mitigation to young children.